The Importance of Organic Content to Fractal Floc Properties in Estuarine Surface Waters: Insights From Video, LISST, and Pump Sampling. Issue 1 (6th January 2021) - Fall, Kelsey A.; Friedrichs, Carl T.; Massey, Grace M.; Bowers, David G.; Smith, S. Jarrell
Abstract: To better understand the nature of flocs of varying organic content in estuarine surface waters, Laser in situ Scattering and Transmissometry, video settling, and pump sampling were deployed in the York River estuary. A new in situ method was developed to simultaneously solve the floc fractal dimension ( F ), primary particle size ( d p ), and primary particle density ( ρ p ) by fitting a simple fractal model to observations of effective floc density (Δ ρ ) as a function of floc diameter ( d f ), while ensuring that the integrated particle size distribution was consistent with measurements of bulk apparent density ( ρ a ). When fractal fits were statistically justified, application of the above methods showed the bulk fraction of organic matter ( f org ) to be well correlated to multiple floc properties. As f org increased, d p and ρ a also increased, while ρ p, total suspended solids (TSS), and median floc size decreased. Notably for microflocs, neither F nor Δ ρ was significantly related to either f org or TSS. This indicates that organic matter may partially displace water content within microflocs without fundamentally changing the flocs' inorganic structure. When pooling multiple samples, a marked decrease in F was seen at the transition to macroflocs, and most strongly for high f org cases. This suggested that settling velocities ≥ ∼1 mm/s may produce turbulent stresses that tend to tear macroflocs apart. This study also found that when the fractal theory held, ρ p had a near 1:1 correlation with the bulk dry density of filtered TSS, implying that primary particles are tightly bound aggregates of combined mineral and organic components. Plain Language Summary: Particles suspended near the surface in estuaries are especially important for estuarine ecology and water quality management, because they can decrease the water clarity by scattering and absorbing the incoming light. Typically, these estuarine particles are not single solid mineral grains, but instead are clusters of inorganic and organic particles and water, called flocs. This study combined observations from water sampling, advanced optical instrumentation, and an in situ video camera to investigate the size, density, and composition of flocs suspended near the surface. It was found that simple mathematical relationships could be applied to describe the key properties of near‐surface flocs, and that the relative amount of organic matter was an important control on the floc characteristics. Key Points: A new method to solve the multiple floc fractal properties by combining laser diffraction, video settling, and pump sampling is presented Organic matter content is an important control on the size and density of primary particles and on the apparent density of microflocs The fractal dimension of microflocs is found to vary less than the primary particle size or primary particle density